2007
DOI: 10.1210/jc.2006-0993
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Thyroglobulin in a Sensitive Immunoassay Has Comparable Sensitivity to Recombinant Human TSH-Stimulated Thyroglobulin in Follow-Up of Thyroid Cancer Patients

Abstract: Patients with differentiated thyroid carcinoma and a T4-suppressed serum Tg below 0.1 ng/ml rarely have a rhTSH-stimulated Tg above 2 ng/ml, and none of these patients had 131I or 123I imaging after rhTSH stimulation suggestive of local recurrence or distant metastasis. We recommend monitoring such patients with a T4-suppressed Tg level and periodic neck ultrasonography. An increase in T4-suppressed serum Tg to a detectable level or the appearance of abnormal lymph nodes by physical or ultrasound exam should p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 18 publications
11
74
0
7
Order By: Relevance
“…Low functional sensitivity Tg assays have a higher sensitivity, but at the expense of a lower specificity (57,58). The future emergence of second generation Tg assays will probably reduce the need of TSH-stimulated Tg measurement in some patients (59).…”
Section: Low Functional Sensitivity Tg Assaysmentioning
confidence: 99%
“…Low functional sensitivity Tg assays have a higher sensitivity, but at the expense of a lower specificity (57,58). The future emergence of second generation Tg assays will probably reduce the need of TSH-stimulated Tg measurement in some patients (59).…”
Section: Low Functional Sensitivity Tg Assaysmentioning
confidence: 99%
“…A further increase to 99% was obtained by coupling onT4-Tg and neck ultrasonography (US) (5). Globally, as confirmed even by using different high-sensitive Tg assays, few patients with undetectable onT4-Tg had a pathological Tg response (i.e., )2 ng/mL) to recombinant human TSH (rhTSH) stimulation, and less actually recurred (6,7). Otherwise, no prospective data are available (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have shown that TSH stimulation is not necessary when using second generation Tg assays with functional sensitivity of 0.1 to 0.3 ng/mL (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%